Determinant of Import in Indonesia - Muhamad Yunanto; Henny Medyawati (Universitas Negeri Malang, 2025)
Trade activities such as imports are a research theme that remains interesting to research. This research was conducted to analyze the effect of inflation, Gross Domestic Products (GDP), Bank Indonesia interest rate (BI rate) and exchange rates for Indonesian imports. This study used quarterly time series data from 2010-2022 from Bank Indonesia and the Central Bureau of Statistics, using the Vector Error Correction Model (VECM) as the estimation tool. The main finding was that, in the short run GDP and inflation has no impact on the import. However, Birate and exchange rate variable has a positive and significant impact on the import. In the long run, the results show that the variables, GDP and BI rate have positive and significant on imports. The main contribution of this research is the use of interest rates (Birate-BI7 Day Reverse Repo Rate) to predict imports which has not been widely used by researchers in Indonesia